Critical Thinking in the Age of Technology from the Perspective of the Qur'an: A Study of Thematic Interpretation - Siti Amanah Istiqamah; Tamrin Tamrin; Kamridah Kamridah; Gasim Yamani (Jurnal Iman dan Spiritualitas, 2026)
The development of digital technology has significantly altered how humans access, process, and evaluate information, reshaping reflection and critical evaluation in modern life. This study examines the concept of critical thinking from a Qur'anic perspective through a thematic (maudhu'i) interpretation approach, focusing on tafakkur and its relevance in the digital era. Using a qualitative library research method, data was analyzed through Peter A. Facione's critical thinking framework, encompassing interpretation, analysis, evaluation, inference, and self-regulation as analytical instruments to read the structure of tafakkur. The results indicate that tafakkur reflects a holistic critical thinking structure that integrates cognitive, spiritual, and epistemological dimensions. Furthermore, the reconstruction of human-machine cognitive relations requires not only modern critical thinking structures but also ethical Qur'anic values. Three primary pillars were identified (mujahadah, tabayyun, and amanah) which function as epistemic and ethical mechanisms to regulate human dependence on technology, ensuring cognitive and spiritual responsibility. Additionally, the Qur'anic concept of taskhir serves as a normative foundation positioning artificial intelligence as a supportive tool rather than a replacement for human intellectual capacity. Thus, this study concludes that integrating tafakkur, Facione’s theory, and the principles of mujahadah, tabayyun, and amanah establishes a new conceptual framework for understanding Qur'anic critical thinking epistemology in the digital era.